PD-loop: A complex of duplex DNA with an oligonucleotide - Bukanov, Nikolay O. (The National Academy of Sciences, 1998)
A stable complex between duplex DNA and an oligonucleotide is assembled with the aid of a DNA synthetic mimic, peptide nucleic acid (PNA). Homopyrimidine PNAs are known to invade into short homopurine tracts in duplex DNA forming P-loops. We have found that P-loops, formed at two closely located purine tracts in the same DNA strand separated by a mixed purine–pyrimidine sequence, merge and open the double helix between them. The opposite DNA strand, which is not bound with PNA, exposes and becomes accessible for complexing with an oligonucleotide via Watson–Crick pairing. As a result, the PD-loop emerges, which consists of locally open duplex DNA, PNA “openers,” and an oligonucleotide. The PD-loop stability and sequence specificity are demonstrated by affinity capture of duplex DNAs by using biotinylated oligonucleotides and streptavidin-covered magnetic beads. The type of complex formed by PNAs, an oligonucleotide and duplex DNA we describe, opens ways for development of various in vitro and in situ hybridization techniques with duplex DNA and may find applications in DNA nanotechnology and genomics.